Preparation of magnesium-calcium titanate powders by alkoxide precursor method - Piagai, R; Kim, IT; Park, JG; Kim, YH (AMER CERAMIC SOC, 1998)
Magnesium-calcium titanate (Mg0.95Ca0.05)TiO3 powders have been prepared via two semialkoxide methods that use nitrate and carbonate precursors instead of magnesium and calcium alkoxides, The thermal decomposition and crystallization behavior of the prepared gels and the morphology of the heat-treated powders have been investigated using thermal analysis, X-ray diffractometry, Fourier transform infrared spectroscopy, and scanning electron microscopy, The ilmenite structure starts to crystallize at a temperature of similar to 500 degrees C without forming an intermediate, spinel-structured phase, Powders obtained from carbonate precursors that have been dissolved in acetic acid reveal a more-spherical morphology and a narrower particle-size distribution than those from nitrate precursors.